P18 ATRIAL FIBRILLATION IN BETA–THALASSAEMIA: PHYSIOPATHOLOGY AND CLINICAL MANAGEMENT. (18th May 2022) - Clò, S; Marchini, F; Sirugo, P; Capanni, A; Malagù, M; Bertini, M; Guardigli, G
Abstract: Beta–thalassaemia is an inherited blood disorder with worldwide distribution characterized by a defective synthesis of haemoglobin. Transfusions and iron–chelation therapy have radically improved the prognosis of beta–thalassaemic patients, while also allowing the development of new chronic complications, cardiac and non–cardiac (diabetes, dystyroidism, autonomic disorders and many others), among which atrial fibrillation (AF) stands out. Prevalence of AF in patients with beta–thalassemia is dramatically higher than in general population, ranging from 2 to 33%. Studies on this topic are lacking and the scarse available evidence comes from a few observational studies. The underlying pathophysiology of AF in thalassaemic is not yet well understood; responsible mechanisms are many (Figure 1 ) and different from those recognized in general population. Atrial iron overload appears to be the main "risk factor", although this arrhythmia may develop even before cardiac siderosis. Clinical presentation is early and mainly paroxysmal, and patients are highly symptomatic. Furthermore, the numerous treatments available for AF (pharmacological and interventional), extensively studied in the general population, are largely unexplored in beta–thalassemia. A specific management is required for these patients (Figure 2 ); in particular, rhythm control should be preferred over rate control, and the most important antiarrhythmic therapy resides in iron–chelating drugs. Thromboembolic risk is also higher than in the general population and the choice of anticoagulant therapy should be considered early (well pondering the serious consequences of a haemorrhage in this setting), but the risk scores available for patients with AF are not validated in the beta–thalassemia.